Telangiectatic Macules Spreading During More Than 30 Years: A Quiz - Italo Francesco Aromolo; Eleonora Di Michele; Francesca Laura Boggio; Angelo Cattaneo; Angelo Valerio Marzano (Medical Journals Sweden, 2024)
Abstract is missing (Quiz)